The impact of genetic variation on IFITM3 related influenza virus restriction - Laurenson-Schafer, H (2018)
The IFITM3 protein is a prominent restriction factor of influenza virus that has been shown to antagonise the cellular entry of influenza virus. In 2012, the minor allele of a synonymous SNP in IFITM3, known as rs12252 (major T, minor C), was shown to be associated with severe influenza virus infection. Numerous studies have corroborated this association, showing clear links between the C allele and increased risk of severe influenza virus infection in East Asian and European populations. It was hypothesised that the observed effects of rs12252-C were related to aberrant splicing of IFITM3, causing an isoform coding for an N-terminally truncated variant of the protein. More recently, additional IFITM3-associated genetic risk factors for severe influenza virus infection have also been uncovered. In this thesis, we investigated the molecular mechanisms of rs12252. In chapter 3, we show that the IFITM3 splicing profile is consistently dominated by the canonical isoform, and that truncated isoforms are produced at extremely low levels regardless of rs12252 genotype. In chapter 4, we investigated associations between rs12252 and expression of IFITM3 at mRNA and protein level, using in vitro systems and healthy donors. We show that rs12252 is an expression Quantitative Trait Locus (eQTL) for IFITM3, and its activity is potentially tissue dependent. We also uncovered potential effects of this SNP on blood transcriptional signature. Next, in chapter 5, we identified two novel eQTLs for IFITM3, which may be risk variants for severe influenza virus infection. Finally, in chapter 6, we analysed the association between rs12252 and severe influenza infection using several model systems. These findings uncovered potential associations between rs12252 and differential interferon signalling, although further experimentation is required to confirm this.